Woman’s Marriage Age in Sharī‘ah: Traditional and Modern Approaches - Nazia Zaman; Dr. Mohyuddin Hashmi (MEI, 2023)
Marriage is called zawāj or nikāh. The word Nikāḥ comes from the Arabic verb nakaha’ which means “to marry”.[i] The time of marriage starts when people feel prepared physically, financially and emotionally. Adolescence is a natural phenomenon that occurs at varying ages in different individuals. The issue among Ulamā and Parliament is “Age” for marriage of woman, is very important and controversial issue in our society. In Sharī‘ah the term “Bulūgh” and “Rushd” are used to determine the age of marriage and different countries based their laws according to the spirit of Sharī‘ah in which a woman would be capable of handling the responsibilities of marriage. In Pakistan the age in different provinces is discussed and recently law is passed to fix the marriage age in Sindh and KPK. In Punjab and federal territory, the Child marriage act amendments are circulated among Parliament, National Assembly, Senate and Council of Islamic Ideology for final decision about fixation of marriage age of women. The Islamization of laws by Modern scholars are criticized by conservative or traditional Ulamā. The aim of the present research is to analyze the issue of marriage age of Muslim women in Pakistan and to study the Traditional and Modern Approaches regarding the matter.